Exploration of KCNJ5 Somatic Mutation and CYP11B1/CYP11B2 Staining in Multiple Nodules in Primary Aldosteronism - Xie, Jing; Zhang, Cui; Wang, Xuefeng; Jiang, Yiran; Wu, Luming; Ye, Lei; Wang, Xuan; Xie, Wen; Xu, Haimin; Wang, Weiqing (Frontiers in Medicine, 2022)
Objective: Unilateral primary aldosteronism (PA) includes aldosterone-producing adenoma (APA), unilateral adrenal hyperplasia and unilateral multiple nodules. The correlation of multiple nodules, especially genotypic and pathological characteristics, remains unknown. KCNJ5 mutation accounts for 60-80% of unilateral PA, so we aimed to explore the correlation of KCNJ5 somatic mutation and CYP11B1/CYP11B2 staining in multiple nodules in unilateral PA. Design and Methods: A total of 56 microdissected nodules from 24 patients with unilateral PA were included. We assessed somatic KCNJ5 mutations, immunohistochemistry for aldosterone synthetase (CYP11B2)/cortisol synthetase (CYP11B1) and histological cellular composition of nodules together with adjacent adrenal cortical statements. Results: KCNJ5 mutations were identified in 17 (17/56, 30.4%) nodules from 11 adrenals (11/24, 45.8%). All KCNJ5-mutant nodules were positive for CYP11B2 staining, 6 cases (6/11) had only one KCNJ5-mutant nodule, and the other 5 cases (5/11) had more than one KCNJ5-mutant nodules. 3 cases (3/11) had different KCNJ5 mutations in individual nodules. Compared with KCNJ5-positive adrenals, the cortices adjacent to the nodules in KCNJ5-negative adrenals showed significant proliferation (P=0.004). CYP11B2/CYP11B1 expression patterns revealed great heterogeneity in intensity and range both in KCNJ5-mutant nodules and KCNJ5-negative ones. Conclusions: There is great heterogeneity among nodules from patients with unilateral PA. Countable nodules could be considered as multiple APAs, featuring somatic KCNJ5 mutation, positive CYP11B2 staining and lack of adjacent cortical proliferation, in unilateral multiple nodules.